2012
DOI: 10.1002/cne.23158
|View full text |Cite
|
Sign up to set email alerts
|

Visual inputs to the mushroom body calyces of the whirligig beetle Dineutus sublineatus: Modality switching in an insect

Abstract: The mushroom bodies are prominent lobed centers in the forebrain, or protocerebrum, of most insects. Previous studies on mushroom bodies have focused on higher olfactory processing, including olfactory-based learning and memory. Anatomical studies provide strong support that in terrestrial insects with mushroom bodies, the primary input region, or calyces, are predominantly supplied by olfactory projection neurons from the antennal lobe glomeruli. In aquatic species that generally lack antennal lobes, the caly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 57 publications
5
38
1
Order By: Relevance
“…R. Soc. B 370: 20150054 the optic lobes to the calyces are also been described in dragonflies [76], the cockroach Periplaneta americana [77,78], the butterfly Pieris rapae [79] and the whirligig beetle Deineutus sublineatus [27]. In most of these insects, the mushroom bodies are large with expanded, often duplicated calyces, much like the mushroom bodies of the social Hymenoptera.…”
Section: Factors Driving Homoplasy In Higher Brain Centresmentioning
confidence: 97%
See 1 more Smart Citation
“…R. Soc. B 370: 20150054 the optic lobes to the calyces are also been described in dragonflies [76], the cockroach Periplaneta americana [77,78], the butterfly Pieris rapae [79] and the whirligig beetle Deineutus sublineatus [27]. In most of these insects, the mushroom bodies are large with expanded, often duplicated calyces, much like the mushroom bodies of the social Hymenoptera.…”
Section: Factors Driving Homoplasy In Higher Brain Centresmentioning
confidence: 97%
“…Interestingly, these structures do not appear to be capable of adapting to a return to an aquatic lifestyle, as olfactory bulbs and antennal lobes are lost or greatly reduced in secondarily aquatic animals such as cetaceans or whirligig beetles [26,27].…”
Section: Homoplasy In Sensory Nervous Systemsmentioning
confidence: 99%
“…Fills into the receptor axons were of 2 h duration, after which whole-cell patch-clamp recording of the GDN culminated in filling it with biocytin, which was subsequently labeled with Streptavidin:Cy3. Using a method described previously by Lin and Strausfeld (Lin and Strausfeld, 2012), after they had been fixed in buffered paraformaldehyde and washed in phosphate buffer, brains were dehydrated, embedded in Spurr's resin (Electron Microscopy Science, Hatfield, PA, USA), sectioned at 20 μm and then mounted in Permount (Fisher Scientific, Fair Lawn, NJ, USA) under thin glass coverslips. Serial sections were scanned with a Zeiss Pascal three-line confocal microscope at increments of 1 μm.…”
Section: Revealing Afferent Inputs To the Gdnmentioning
confidence: 99%
“…An interesting aspect is the fact that in some insects the mushroom bodies have been found to process visual input, either as part of a complete modality switch (Lin and Strausfeld, 2012) or by topographical division of the different modalities into separate areas (Kinoshita et al, 2014). The distinct projections of olfactory neurons into the outer layers of the hemiellipsoid body in stomatopods could suggest that the inner core could have a different function, perhaps processing visual information?…”
Section: Hemiellipsoid Bodiesmentioning
confidence: 99%
“…These hemiellipsoid bodies have been suggested to be homologues of the mushroom bodies in insects and morphology, ultrastructure and immunoreactivity advocate the same (Wolff et al, 2012). Recent studies have also revealed that the mushroom bodies are capable of modality switching, processing visual information instead of olfactory information in aquatic species which generally lack antennal lobes (Lin and Strausfeld, 2012).…”
Section: Introductionmentioning
confidence: 97%